COST Action “Investigation and Mathematical Analysis of Avant-garde Disease Control via Mosquito Nano-Tech- Repellents” (IMAAC) CA16227 (2017—2021) - Peyman Ghaffari; Ana Marija Grancaric (Textile & Leather Review, 2019)
The main aim and objective of the Action is to address the quantitative and mathematical investigation of the effect of employing avant-garde mosquito control measures as part of the technological processes in the textile and paint industries. The measurement of these effects in population to improve the new generation of control measures is the core of this challenge.